2015
DOI: 10.1194/jlr.m061903
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of antigen extends the durability of an anti-PCSK9 monoclonal antibody

Abstract: This article is available online at http://www.jlr.org atherosclerosis ( 7,8 ). Conversely, loss-of-function mutations are associated with reduced LDL-C and reduced risk of cardiovascular diseases ( 9-11 ).PCSK9 is expressed in multiple tissues, including liver, intestine, kidney, and cerebellum, of which the liver appears to be the major source of the circulating protein (12)(13)(14). It is synthesized as a 74 kDa proprotein, which is activated prior to secretion by the autocatalytic cleavage of its N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…This reduced accumulation of LY may reflect a difference in LY binding to PCSK9 compared with other PCSK9 antibodies in development. 4 , 5 As the LY-binding epitope does not include the furin cleavage site, the antibody may bind while allowing normal proteolytic degradation of PCSK9, minimizing accumulation of PCSK9. 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduced accumulation of LY may reflect a difference in LY binding to PCSK9 compared with other PCSK9 antibodies in development. 4 , 5 As the LY-binding epitope does not include the furin cleavage site, the antibody may bind while allowing normal proteolytic degradation of PCSK9, minimizing accumulation of PCSK9. 11 …”
Section: Discussionmentioning
confidence: 99%
“…LY3015014 (LY) is a humanized immunoglobulin G4 (IgG4) monoclonal antibody characterized by a comparatively long duration of action demonstrated in preclinical studies. 4 , 5 The durability in LDL-C reduction may result from LY binding to a site that permits normal proteolytic cleavage of PCSK9, which may result in a reduction of target-mediated drug disposition. Based on these data, we hypothesized that administration of LY every 8 weeks might be sufficient for LDL-C reduction and offer a significant dosing advantage over other anti-PCSK9 antibodies that require dosing every 2 or 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the fact that PCSK9 is inactivated by some proteases such as furin (Benjannet et al, 2006;Essalmani et al, 2011) might open new strategies to enhance this inactivation mechanism, and thus lower the levels of active PCSK9. Indeed, recently a new mAb was reported that inhibits PCSK9 activity but still allows furin to inactivate it, resulting in a longer halflife of the antibody (Schroeder et al, 2015). The future will tell which strategies targeting PCSK9, including longer lasting mAbs, RNA interference (Fitzgerald et al, 2014), and small-molecule inhibitor approaches (Seidah, 2013), will find their way in dyslipidemia, cardiology, and sepsis in clinics worldwide, which would result in affordable and safe treatments and/or prevention of lifethreatening conditions.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…We recently described a PCSK9 antibody with a novel mechanism of action. 11 Unlike other reported catalytic domain PCSK9 inhibitory antibodies, LY3015014 (LY) binds to a PCSK9 epitope that allows cleavage of the intact active form of PCSK9 to the inactive, 52-kDa form by protease cleavage at Arg218 in the catalytic domain. LY binds N-terminally to the cleavage site, so LY will bind and inhibit full-length (FL) PCSK9 binding to LDL-receptor, but since it allows cleavage of the protein, FL PCSK9 levels do not accumulate in the serum of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…Other PCSK9 antibodies caused significant accumulation of FL PCSK9 in humans and animals. 11,12 It was shown that LY allowance of PCSK9 cleavage led to increased potency and durability of effect on LDL-C levels compared with antibodies that did not allow this cleavage. It was also shown that PCSK9-mediated clearance of LY was diminished relative to other anti-PCSK9 antibodies.…”
Section: Introductionmentioning
confidence: 99%